Allergy and Spirituality - Barron, Earle P. (Journal of pastoral care & counseling, 2010)
This article considers the relationships of allergic reactions to substances and emotions. It deals with spiritual sensitivity as well. Resistance is a key to allergic reactions: Allergic reactions involve the body's resistance to substances, emotions, and their energies. A major problem in spiritual formation is resistance to giving up the prideful and self-centered position and moving into loving relationships. It is sometimes possible from an alternative approach to promote spirituality by treating allergy. In spiritual formation, one may sometimes decrease allergic tendencies by giving up pride and other negative emotions. I propose that the alternative method I advocate not only reduces symptoms but deals with causes on an energetic level. It works with physical, emotional and spiritual factors. It provides new ways for counselors and spiritual directors to quickly get to basic issues and clear negative emotions and beliefs. This may be accomplished within or in connection with the therapists' or directors' particular religions, practices and/or therapeutic approaches.